(untitled) (Praxis Educativa, 2020)
The COVID-19 pandemic has created unprecedented conditions in all areas of social life and as the suspension of schooling became “the new normal,” numerous experts and opinion-makers rushed to voice their recommendations to governments and educational organizations for normalizing schooling operations. In light of this worldwide crisis, we re-evaluate proposals to expand the model of Global Citizenship Education (GCE) that have received increasing attention and support from both international organizations, governments, and scholars. In this article, we argue that the predominately redemptive nature of GCE models and proposals since the mid-1990s cannot handle global problems associated with the current pandemic such as the restriction of citizen’s privacy rights or the strengthening of exclusionary nationalistic messaging. Instead, more realistic models of GCE are needed. This paper concludes with new questions to strengthen the debate and alternatives for imagining a non-redemptive and more realistic GCE. Keywords: Global Citizenship Education. COVID-19 pandemic. Redemptive pedagogies.